Use of Information Technologies in Improving the Quality and Efficiency of Physical Education Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article in order to improve the quality and efficiency of physical education lessons, the issues of using information technologies and Internet resources are highlighted.